2020
DOI: 10.1021/acs.jmedchem.0c00734
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Acetazolamide-Based Scaffold as Potent Inhibitors of Vancomycin-Resistant Enterococcus

Abstract: Vancomycin-resistant enterococci (VRE) are the second leading cause of hospital-acquired infections (HAIs) attributed to a drug-resistant bacterium in the United States, and resistance to the frontline treatments is well documented. To combat VRE, we have repurposed the FDA-approved carbonic anhydrase drug acetazolamide to design potent antienterococcal agents. Through structure–activity relationship optimization we have arrived at two leads possessing improved potency against clinical VRE strains from MIC = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 96 publications
(188 reference statements)
2
81
0
Order By: Relevance
“…[1][2][3] As a response, the scientific community has engaged an in-deep search of new druggable targets, which are essential for the virulence and/or life cycle of pathogens considered. [3][4][5] In this context, the metalloenzymes Carbonic Anhydrases (CAs, EC 4.2.1.1) are particularly attractive. [2,[6][7][8] Bacteria encode four different CA genetic classes, namely the α-, β-, γand ι-CAs, which show a variegate distribution among the various strains [2,7b] as well as structural differences.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As a response, the scientific community has engaged an in-deep search of new druggable targets, which are essential for the virulence and/or life cycle of pathogens considered. [3][4][5] In this context, the metalloenzymes Carbonic Anhydrases (CAs, EC 4.2.1.1) are particularly attractive. [2,[6][7][8] Bacteria encode four different CA genetic classes, namely the α-, β-, γand ι-CAs, which show a variegate distribution among the various strains [2,7b] as well as structural differences.…”
Section: Introductionmentioning
confidence: 99%
“…More exciting is the discovery that ethoxzolamide can kill H. pylori in vitro and in vivo, and that the bacterial resistance to this compound does not develop easily. The recent study on the efficacy of acetazolamide and some of its derivatives to act as inhibitors of vancomycin resistant enterococci (VRE) is a breakthrough in the field (Kaur et al, 2020). The drug design campaign reported in the same study led to the identification of sulfonamide derivatives, which seem to be orders of magnitude more efficient against VRE, when compared to the clinically used agent linezolid.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, EZA resistance did not develop easily in the H. pylori strains (P12, SS1,m and 26695) used for the experiments, and the compound seems to target multiple pathways since resistance acquisition was due to mutations associated with other genes than CAs (Rahman et al, 2020). In this context, we stress the fact that, recently, it has been demonstrated that the well documented vancomycinresistant enterococci (VRE) might be addressed by targeting the Enterococcus CAs using a modified scaffold of acetazolamide (an inhibitor of the carbonic anhydrases) (Kaur et al, 2020). As a result, the authors identified two lead compounds having improved potency against clinical VRE strains (MIC from 0.007 to 1 µg/mL) (117).…”
Section: In Vivo Ca Inhibitionmentioning
confidence: 99%
“…In fact, both CA inhibitors (CAIs) [5][6][7][8] , and CA activators (CAAs) 9,10 have many therapeutic applications in a variety of fields, starting with diuretics and antiglaucoma agents and ending with anticancer/antimetastatic drugs (for the inhibitors) 5-8 , but also including memory therapy, modulation of emotional memory and fear extinction memory activator agents 9,10 . Recently, inhibition of CAs from pathogenic organisms has also been proposed as an innovative approach to develop anti-infectives, which may target bacterial infections resistant to clinically used antibiotics 4,[11][12][13] , but also to treat protozoan-provoked 14,15 as well as fungal infections 16,17 . Indeed, various classes of inhibitors were shown to be effective in a variety of models 4,[11][12][13][14][15][16][17] , which inspired researchers to find novel chemotypes acting as modulators of activity as well as novel potential drug targets 4,[11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inhibition of CAs from pathogenic organisms has also been proposed as an innovative approach to develop anti-infectives, which may target bacterial infections resistant to clinically used antibiotics 4,[11][12][13] , but also to treat protozoan-provoked 14,15 as well as fungal infections 16,17 . Indeed, various classes of inhibitors were shown to be effective in a variety of models 4,[11][12][13][14][15][16][17] , which inspired researchers to find novel chemotypes acting as modulators of activity as well as novel potential drug targets 4,[11][12][13][14][15][16][17] . Very recently, a gene coding for a member of the i-CA family has been originally described to occur in the genome of the marine diatom Thalassiosira pseudonana 2a ; the corresponding enzyme has been isolated and reported preferring Mn(II) as a metal cofactor in its active site, and not Zn(II) frequently found therein in other organisms.…”
Section: Introductionmentioning
confidence: 99%